Analysis of carbon emission efficiency based on DEA model. (17th February 2018) - Zhu, Jing
Abstract: This paper collects the amount of the energy consumption, fixed assets, labor input and GDP data from 2004 to 2014 in Shijiazhuang City, to calculate carbon emissions of Shijiazhuang each year, and to measure the level of carbon emission efficiency in Shijiazhuang City using the DEA model and fixed assets, labor input, carbon emissions as input indicators, GDP as output indicators.